Sexual violence against women in popular cinema: the case of fifty shades of grey and elle - Abduljalil, Latifah Qasem Hamood (My University, 2019)
Bu tez ile ulaşılan sonuçlardan biri, sinemanın cinsel şiddeti güzelleştirdiği ve sinema ile kadının cinsel yöneliminin, kendine saygısının ve bedenini sunuşunun çarptırıldığıdır. Sinema kadınlara cinsel şiddetin zevk unsuru olabileceğini göstermesine rağmen, aslında gerçek cinsel şiddetten zevk alan kadınların kendinden nefret eden kişiler olduğu sonucudur. Kadının cinsel imajı problemli çocukluk dönemi geçiren güçlü feminist figürler ile onur kırıcı bir duruma sokulmuştur. Böylelikle tecavüz ve mazoşizm mitleriyle ilgili varsayımlar desteklenmiştir. Sinema kadınları röntgencilik kurbanı olmaktan cinsel şiddet mağduru şekline çevirerek daha kapsamlı bir kurban yaratmıştır.

This study concludes that the cinema attempted to prettify sexual violence practices and distort the concepts of women's sexual control, her self-esteem and the way she embraces her body, and how the cinema persuades women to remain violated could be a pleasurable choice while it is only a reflection of self-loathing, and the persistence of cinema in creating degrading sexual images of women reflected by strong feminist figures with troubled childhood, supporting assumptions about rape and masochism myths and keeping women inside a more comprehensive perspective of victimization, from being a victim of voyeurism to become a victim of sexual violence acts.
Keywords: Cinema; Cinsel Şiddet; Elle; Feminism; Fifty Shades of Grey; Grinin Elli Tonu; Kadın; Masochism; Mazoşism Sexual Violence; O Kadın; Psikoloji; Psychology; Sinema; Women